Perlindungan Konsumen Terhadap Penjualan Obat Antibiotik Tanpa Resep Dokter - Hubertus Veron Mailuhuw; Theresia Louize Pesulima; Yosia Hetharie (PATTIMURA Law Study Review, 2023)
ABSTRACT: Drugs are a very important component for public health, meaning that drugs are needed to cure diseases suffered by humans. One of them is an antibiotic drug which is a drug to kill bacteria in the body and to increase endurance. In the provisions of the Regulation of the Minister of Health Number 73 of 2016 which regulates Pharmaceutical Service Standards, as well as Decree of the Minister of Health of the Republic of Indonesia No. 02396/A/SK/VIII of 1986 concerning Special Marks for List G Strong Drugs stipulates that antibiotic drugs as a category of hard drugs on list G can only be given with a doctor's prescription with sufficient criteria. However, in practice it is still traded freely without a doctor's prescription by pharmacies. This certainly violates consumer rights in Article 4 letter a regarding the right to comfort, security and safety in consuming goods and/or services. The pharmacist's actions also contradict Article 7 letter b of the UUPK's obligation as a business actor to provide correct, clear and honest information regarding the conditions and guarantees of goods and/or services as well as provide an explanation for the use of antibiotic drugs. The method used in this study is normative juridical, with a statutory approach and a conceptual approach. The legal materials used are primary and secondary legal materials collected through literature study, and analyzed qualitatively to answer the problems studied. Based on the results of the study, those responsible for the sale of antibiotic drugs without a doctor's prescription are the pharmacy companies because legally the pharmacies know exactly and clearly about the provisions prohibiting the sale of antibiotic drugs without a doctor's prescription. This means that if consumers want to buy antibiotics, it is the responsibility of the pharmacy to explain correctly and clearly regarding the provisions for using antibiotics that must be prescribed by a doctor, not vice versa to seek profit and then ignore consumer safety. The legal liability that can be imposed on the pharmacy is liability based on fault, so the pharmacy must provide compensation to consumers (buyers) if it is proven that due to their mistakes they caused harm to the buyer through the misuse of antibiotic drugs which can lead to overdose, resistance even death.